The effect of torrefaction temperature on combustion and chemical composition of wood waste pellet - Najaatul Aimi, Sollahunddin; Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (AIP Publishing, 2025)
The abundance of renewable energy sources in Malaysia has prompted the expansion of the national biomass strategy beyond the oil palm industry to include resources like rubber, wood, and rice husk. However, despite the potential of wood waste as an energy resource, its drawbacks, such as high moisture content, low energy density, and a high O/C ratio, could limit its efficiency compared to fossil fuels. Hence, the torrefaction process is employed to improve the unfavorable characteristics of wood waste by heating the biomass under inert conditions. However, the resulting bulk form of torrefied biomass requires a pelletization process for easier storage and transportation. Thus, the objective of this study is to investigate the effect of torrefaction temperature on the chemical compositions and combustion behavior of torrefied biomass pellet. Two different wood wastes were used in this study, which are Meranti and Resak. The samples undergo torrefaction process at three different temperatures (240, 270 and 300°C) for 30 minutes. After that, the torrefied wood was mixed with palm oil mill effluent (act as binder) prior to pelletization process. Pelletization process was conducted at 150°C for 20 minutes. Then, the torrefied pellets were combusted under bunsen burner for approximately 5 minutes to ensure complete combustion of torrefied pellets and after that the torrefied pellets undergo FTIR analysis to investigate changes in chemical composition. The result from the mass yield shows a slight difference at 240°C and 270°C, but a significant decrease at 300°C. Based on combustion experiments, there are three main stages during decomposition of pellets which are gasification, flame burning and char burning. Meanwhile, FTIR analysis shows that with increase of torrefaction temperature, the hydroxyl and methoxyl groups were decomposed thus decreasing the amount of oxygen and hydrogen contents. In conclusion, the addition of POME as a binder did not significantly alter the chemical composition of the torrefied pellets.